ENVIRONMENTAL AWARENESS AND SOLID WASTE MANAGEMENT IN STUDENTS OF THE SAN IGNACIO DE LOYOLA PRIVATE EDUCATIONAL INSTITUTION IN 2022 (LACCEI, 2024)
Abstract: One of the biggest challenges facing society in the 21st century is environmental pollution, damage to nature, overexploitation of natural resources, among others, in this sense engineering plays an important role in solving problems. , responding to the demands through environmental engineering, which seeks to provide tools to professionals to improve care for the environment, however we consider that we must do an articulated job from educational institutions, working to raise awareness among students from early stages of their student development. The objective of the research seeks to determine the relationship between awareness and environmental management of solid waste in the San Ignacio de Loyola Private Educational Institution - located in the Vipol urbanization, Callao, in 2022. The research methodology is correlational with a quantitative approach and non-experimental design. The sample is not census probabilistic of 61 high school students. The results were obtained from the SPSS statistical program and Spearman's Rho coefficient to verify the hypothesis, it was concluded that there is a relationship between the variables of environmental awareness and solid waste management, with 0.627 of moderate positive consequences according to the Spearman's Rho coefficient, showing a relationship is very significant with a confidence of 99%.